2019
DOI: 10.1609/aaai.v33i01.33011198
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Network Analysis with Discriminative Hub Detection for Brain Disease Identification

Abstract: Brain network analysis can help reveal the pathological basis of neurological disorders and facilitate automated diagnosis of brain diseases, by exploring connectivity patterns in the human brain. Effectively representing the brain network has always been the fundamental task of computeraided brain network analysis. Previous studies typically utilize human-engineered features to represent brain connectivity networks, but these features may not be well coordinated with subsequent classifiers. Besides, brain net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Resting-state functional magnetic resonance imaging (rs-fMRI) provides a non-invasive measure of brain activity and attracts considerable attention for understanding the brain organization (Bijsterbosch et al, 2017 ; Zhang et al, 2020 ). Function brain network (FBN) derived from rs-fMRI scans has been increasingly employed to computer-aided diagnosis of brain disorders, such as autism spectrum disorder (Jie et al, 2018a ; Wang et al, 2019a , c ; Wen et al, 2019 ; He et al, 2020 ), Alzheimer's disease (AD) and its prodromal stage (i.e., mild cognitive impairment, MCI) (Stam, 2014 ; Fornito et al, 2015 ; Liu M. et al, 2015 ; Jie et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) provides a non-invasive measure of brain activity and attracts considerable attention for understanding the brain organization (Bijsterbosch et al, 2017 ; Zhang et al, 2020 ). Function brain network (FBN) derived from rs-fMRI scans has been increasingly employed to computer-aided diagnosis of brain disorders, such as autism spectrum disorder (Jie et al, 2018a ; Wang et al, 2019a , c ; Wen et al, 2019 ; He et al, 2020 ), Alzheimer's disease (AD) and its prodromal stage (i.e., mild cognitive impairment, MCI) (Stam, 2014 ; Fornito et al, 2015 ; Liu M. et al, 2015 ; Jie et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to previous studies that rely on pre-defined FC networks (e.g., via Pearson's correlation) (Wee et al, 2016;Jie et al, 2018;Wang et al, 2019aWang et al, , 2022, the proposed method can generate dynamic FC networks in a data-driven manner. We now investigated the FC networks constructed by the proposed TDNet in the KKI site.…”
Section: Constructed Functional Connectivitymentioning
confidence: 99%
“…It has been reported that FBN generally has more topological structures than just sparsity (Meunier et al, 2009;Zhao et al, 2012;Sporns, 2016;Wang et al, 2019a;Wen et al, 2019). For example, one of the most representative structure is modularity that is believed to be extremely important for promoting stability, conserving wiring cost, and enabling complex neuronal dynamics of our brain.…”
Section: Figurementioning
confidence: 99%